Equitable distribution of open space: Using spatial analysis to evaluate urban parks in Curitiba, Brazil. (November 2016) - Macedo, Joseli; Haddad, Mônica A
Urban parks are community assets, providing people places to play and rest. Access to parks in urban environments promotes social equity and improves quality of life for surrounding neighborhoods. In this context, social equity is related to accessibility, i.e. the possibility of walking or biking from home to a public park, giving people who do not have access to a variety of entertainment an option that is a public good. This paper examines the spatial distribution of urban parks in the city of Curitiba, Brazil, and how it relates to the socio-economic conditions of surrounding neighborhoods. Curitiba is known for its urban parks; however, no systematic study has been conducted to verify which neighborhoods enjoy park access within walking distance and what the socio-economic differences are between the better and worse served neighborhoods. In addition, we investigate if access to green open space has improved between the last two decennial census, a period marked by unprecedented socio-economic affluence in Brazil. Research questions, to be addressed using spatial analysis, focus on equitable distribution, and spatial evolution of parks and social equity. Variables include measurable walking distances from census tracts to parks, income data from the 2000 and 2010 Brazilian decennial censuses, and qualitative data of urban parks in Curitiba. Findings offer recommendations for future implementation of additional parks in Curitiba so that all areas of the city have adequate green open space and all citizens have equal access to recreation and leisure opportunities.